Practical assessment of work-level in equines - Ellis, Andrea D (MTT, 2008)
Energy evaluation systems apply a varying range of methods for the practitioner to estimate energy requirements above maintenance for working horse. Current systems generally incorporate some measure of intensity and duration but repetition, different training sessions or additional effort are generally neglected. As these systems try and cover every aspect of horse sport, rider level and training schedule these general tables can only remain very rough guides. This paper introduces a possible method incorporating the best of current systems with a novel approach for practical application. The work level system reported here has been developed to incorporate methods used in all systems but also to allow further depth in evaluation for the lay person. It attempts to bring together the best of current systems a novel approach for practical application. Exercise levels are evaluated for individual types of exercise (e.g. lunging, hacking out, schooling, jump-schooling, dressage etc.). Once these have been determined the horse trainer needs to put down 4 scores for each exercise type undertaken per week. To assess exercise levels per type of training a duration score and intensity score has been developed. There is a good correlation between recent formulas incorporating heart rate and oxygen consumption and the proposed work level system. This means layperson can assess work levels of their horses much more accurately without the use of a calculator or complicated formulas. In practice, body condition score will be used primarily to assess if horses receive the correct energy required from their feed. However, generally ration calculations are not carried out in detail unless there is either a problem with body condition, health or performance. In these cases evaluating exercise levels correctly is important as these form the basis for assessing the protein, mineral and vitamin requirements of horses.
Keywords: Ko; equine work level; energy requirements; training programmes